White men have systematic advantages in science. (1st August 2022) - Allen, Michael
Abstract : Survey data from more than 25, 000 STEM professionals in the US suggests that white able-bodied heterosexual men working in science, technology, engineering and maths (STEM) are uniquely privileged and experience a wide range of advantages at work compared with other groups.